2013
DOI: 10.1631/jzus.b1200195
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Akt and cardioprotection against reperfusion injury are maximal with only five minutes of sevoflurane postconditioning in isolated rat hearts

Abstract: It had been proved that administration of sevoflurane for the first two minutes of reperfusion effectively protects the heart against reperfusion injury in rats in vivo. Our aim was to investigate the duration of effective sevoflurane administration and its underlying mechanism in isolated rat hearts exposed to global ischemia/reperfusion (I/R) injury. Adult male Sprague-Dawley rats were randomly divided into six groups (n=12): a sham-operation group, an I/R group, and four sevoflurane postconditioning groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Ischemic post-conditioning has several clinical advantages, including predictability, controllability and safety ( 3 ). It has recently been reported that inhalation anesthetics administered at the beginning of reperfusion provides cardioprotection against I/R injury ( 4 ). Sevoflurane is widely used in cardiac surgery since it has the advantages of shorter induction, reduced recovery time and higher safety when compared with other anesthetics ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic post-conditioning has several clinical advantages, including predictability, controllability and safety ( 3 ). It has recently been reported that inhalation anesthetics administered at the beginning of reperfusion provides cardioprotection against I/R injury ( 4 ). Sevoflurane is widely used in cardiac surgery since it has the advantages of shorter induction, reduced recovery time and higher safety when compared with other anesthetics ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that sevoflurane reduces myocardial infarct size and mortality in both animals ( 6 , 7 ) and humans ( 8 ). It has been suggested that a variety of molecular mechanisms may be responsible for the protective effects of sevoflurane, including phosphatidylinositol 3-kinase (PI3K)/Akt pathway activation ( 4 , 9 ), reactive oxygen species (ROS) regulation ( 10 ) and mitochondrial permeability transition pore (MPTP) inhibition ( 11 ). However, the exact mechanisms through which sevoflurane post-conditioning reduces MIRI remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of myocardial eNOS and p-eNOS were determined by Western blotting as previously described. [30][31][32] …”
Section: Determination Of Myocardial P-enos Expressionmentioning
confidence: 99%
“…Studies have shown that inhalation a certain amounts of anesthetics before ischemia or at the beginning of reperfusion can inhibit MIRI, and protect the myocardium ( 5 ). Sevoflurane exhibits several advantages such as short anesthesia induction and recovery time, less irritation, a high safety profile and adjustable depths of anesthesia, and is therefore widely used in cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%